PENINGKATAN KEMAMPUAN BERPIDATO DENGAN MENERAPKAN PENDEKATAN KOMUNIKATIF DAN METODE LATIHAN PADA SISWA SMP - Yuliantoro, Prima; Heryana, Nanang; Syambasril, Syambasril (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstrakThe background of this research is because of the ability of Year-9 Students of SMPIT Al-Mumtaz Pontianak in Speaking Skill especially for Speech is Low. Researcher is focused on this research problem to process and the result of learning using Approach of Comunicative and Assessment Method. The kind of reseach is Class Action Research (CAR) that was implied in two cycles. The method and the form in this research using qualitative description. Data source of this research is Indonesia’s language teacher and the population is 34 students. Data in this research is the process and the result Speech assessment. The technique is implemented in this research adalah Non-test technique through observation and documentation. The result of this research indicates that before using Approach of Comunicative and Assessment Method ,the average of students score is 65. The sudents score of speech in the first cycle using Approach of Comunicative and Assessment Method was increasing with the average score 68,3. Meanwhile, the average score in the second cycle is 80,5. Based on the result of student speech from the first cycle to the second cycle has increased.Keyword : Speech, Communicative Approach, Assesment Method